Measurement of steep edges and undercuts in confocal microscopy. (May 2016) - Mueller, T.; Jordan, M.; Schneider, T.; Poesch, A.; Reithmeier, E.
Abstract : Highlights: Characterization of the influence of steep edges and undercuts on the confocal microscopy measurement result for technical surfaces. Introduction of an algorithm to avoid the negative influence of steep edges and undercuts. Introduction of a simulation method for microscopic topography measurements for a better understanding of the measurement results. Abstract: Confocal microscopy is widely used to measure the surface topography of specimen with a precision in the micrometer range. The measurement uncertainty and quality of the acquired data of confocal microscopy depends on various effects, such as optical aberrations, vibrations of the measurement setup and variations in the surface reflectivity. In this article, the influence of steep edges and undercuts on measurement results is examined. Steep edges on the specimen's surface lead to a reduced detector signal which influences the measurement accuracy and undercuts cause surface regions, which cannot be captured in a measurement. The article describes a method to overcome the negative effects of steep edges and undercuts by capturing several measurements of the surface with different angles between the surface and the optical axis of the objective. An algorithm is introduced which stitches different angle measurements together without knowledge of the exact position and orientation of the rotation axis. Thus, the measurement uncertainty due to steep edges and undercuts can be avoided without expensive high-precision rotation stages and time consuming adjustment of the measurement setup.